Mental Health Psychoeducation to Develop Elderly’s Psychological Welfare in Mandalamekar Village Cimenyan District - ., Suhana; Susandari, Temi Damayanti; Hatta, Muhammad Ilmi Hatta; Andriane, Salsa Altasya; Sofwan, Anisa; Syahrizal, Arie; Alimiyah, Wildah Sifa (KnE Social Sciences, 2023)
Old age is characterized by various physical and psychological changes, which can significantly impact how seniors adapt to their circumstances. However, it is more likely that the characteristics of old age lead to positive adjustments rather than negative ones, and contribute to happiness rather than misery. Despite this, loneliness remains a prevalent psychological disorder experienced by the elderly. Several factors, such as children becoming adults and leaving for school or the death of a spouse, can contribute to feelings of loneliness. To address this issue, treatment for loneliness is necessary. Group counseling and religious psychoeducation are effective methods employed to tackle loneliness among the elderly. Through group counseling and religious psychoeducation, the elderly can experience a sense of togetherness and openly discuss the problems they face. The religious psychoeducation sessions, focusing on patience and prayer, aim to instill new hopes and coping strategies to address their challenges. The UCLA Loneliness Scale version 3 is used to measure the level of loneliness in the elderly participating in this service. The results demonstrate that group counseling and religious psychoeducation have a positive impact, leading to a decrease in the level of loneliness experienced by the elderly. This is evident from the paired t-test results, indicating a significance value of 2 tailed below 0.05. Keywords: loneliness, patience, group counseling, religious psychoeducation, elderly